The consolidation of the evaluative state through accountability policies: Trajectory, enactment and tensions in the Chilean education system - Parcerisa, Lluís; Falabella, Alejandra (Education Policy Analysis Archives, 2017)
Chile is a particularly interesting case to study the introduction of accountability policies. During the 2000s decade, Chile intensified these measures to try to address the failures of a highly deregulated school market system. This article examines the adoption process of accountability policies and the consolidation of the Evaluative State through the construction of the National System of Quality Assurance of Education during the period 2006-2011. Theoretically, the article is based on the “politics and semiotics of policy adoption” approach. Methodologically, it examines documents associated with the policy (official speeches, laws, parliamentary discussions, reports, governmental documents), and draws on 27 semi-structured interviews with those involved in the production of the policy (policy-makers, Ministry officials, parliamentarians, advisers and technicians). The article examines the development of the policy process, the factors that opened a “window of opportunity” to consolidate the accountability model, the discursive disputes that emerged during the deliberation process, and the emergence of accountability policies as a policy approach that seduced both the right and the center-left.